DISCOVERY AND CHARACTERIZATION OF NOVEL BETA-LACTAMASE INHIBITORS - King, Andrew M. (My University, 2016)
The discovery of antibiotics and their subsequent clinical use has had a tremendous and beneficial impact on human health. The β-lactam antibiotics, which include penicillins, cephalosporins, carbapenems, and monobactams, constitute over half of the global antibiotic market. However, like all antibiotics, the β-lactams are susceptible to bacterial antibiotic resistance. One of the most disconcerting manifestations of bacterial resistance to β-lactam antibiotics is the evolution and dissemination of β-lactamases, enzymes able to chemically inactivate β-lactam antibiotics. These resistance determinants are the key contributing factor to extensively-drug resistant Gram-negative pathogens, for which we are already bereft of chemotherapeutic treatment options in some cases. The coadministration of a β-lactamase inhibitor (BLI) with a β-lactam antibiotic is a proven therapeutic strategy to counter β-lactamase expression. Unfortunately, the emergence of both serine β-lactamases (SBLs) that are resistant to BLIs and metallo-β-lactamases (MBLs), which are intrinsically resistant to BLIs due to a discrete mechanism of β-lactam hydrolysis, threaten the efficacy of combination therapy. Notwithstanding this bacterial adaptation, the discovery and development of novel BLIs is an attractive strategy to evade resistance, as evidenced by the recent clinical approval of the diazabicyclooctane (DBO) SBL inhibitor, avibactam. Herein, I describe efforts directed at understanding the mechanism of avibactam SBL inhibition. Furthermore, DBO derivatives are shown to display bifunctional properties in inhibiting both β-lactamases and the targets of β-lactam antibiotics, the penicillin-binding proteins. In addition to understanding the enzymology and chemical biology of DBOs, I describe two screening campaigns directed towards discovering inhibitors of MBLs, an unmet clinical need. Using target and cell-based screening of both synthetic and natural product chemical libraries, a fungal natural product inhibitor of clinically relevant MBLs was discovered and characterized. This study expands our understanding of the mechanisms by which DBOs can be used to combat extensively drug-resistant Gram-negative pathogens. It also describes the discovery of a new natural product MBL inhibitor using a workflow that should be amenable to other resistance determinants. It’s hoped that these studies can contribute meaningfully to countering antibiotic resistance observed in clinical settings.
Keywords: Chemical Biology; Antibiotic Resistance